PENERAPAN METODE FMEA DAN SIX SIGMA DMAIC DALAM UPAYA PENGURANGAN CACAT PRODUK KARET RSS (RIBBED SMOKE SHEET) DI PTPN 4 REGIONAL 1 - Pratama Pebrina Br. Tarigan, Uni; Marpaung, Nauly Paula Oktavia; Kurniawati, Lusy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The RSS rubber products produced in the production process at PTPN IV Regional 1 still show defects that affect product quality. This condition requires an analysis to identify the types of defects, their contributing factors, and appropriate improvement efforts. This study aims to analyze defects in RSS rubber products using the Six Sigma method with the DMAIC approach and to determine improvement priorities using the Failure Mode and Effect Analysis (FMEA) method. The data used consists of production data and data on the number of product defects, which include bubble defects, stains, and burns. Data processing is carried out through the stages of define, measure, analyze, improve, and control. The results of the analysis show that bubble defects are the type of defect with the highest percentage. Based on FMEA calculations, bubble defects have a Risk Priority Number (RPN) value of 320, followed by stain defects with 196 and burn defects with 162. The results of the study indicate that the main causes of defects come from irregularities in the mixing process, environmental cleanliness conditions, and inconsistencies in temperature and smoking time. Improvement efforts are carried out through process parameter control, improving workplace cleanliness, implementing degassing, and enhancing operator competency. The application of the Six Sigma DMAIC method is able to provide a systematic approach in identifying and reducing the level of defects in RSS rubber products.